Implementation of Science, Technology, Engineering, Art, and Mathematics (STEAM) Learning Model on Wayang Puppet Materials to Improve Student Creativity in the 21st Century - Yopi Malagola; Eryneta Nurul Hasanah; Siti Nurjannah (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2023)
This research is motivated by learning that only uses the lecture method, causing students to lack interaction and creativity on wayang puppet material in elementary schools. In addition, the lack of implementation of science, technology, engineering, art, and mathematics (STEAM) learning in elementary schools also impacts the achievement of learning outcomes. Therefore, this study aims to determine the increase in student creativity by applying the STEAM model to wayang puppet learning in elementary schools. The type of research used is classroom action research (CAR), carried out in two cycles. Each cycle has four stages: planning, implementation, observation, and reflection. The subjects of this research are the fourth-grade students of Muhammadiyah Suronatan Elementary School, Yogyakarta, with a total of 20 people. Data collection techniques were carried out through observation, questionnaires, and documentation. The analytical technique used in this research is descriptive qualitative analysis. The results of this study indicate that the application of the STEAM learning model to wayang puppet materials can increase the creativity of fourth-grade students at Muhammadiyah Suronatan Elementary School, Yogyakarta. This is evidenced by the results of cycle 1, where the percentage of student creativity reaches 50%, and the percentage of student creativity increases in cycle 2, reaching 85%.